Assistência pré-natal no Ceará na perspectiva do Programa de Humanização no Pre-Natal e Nascimento - Passos, Anderson Aguiar (2006)
Pregnant women’s access to a decent, humanized and qualified service is not only a right, but a women’s necessity. The Health Department expresses and makes official through regulations, the intention of investing in attention to pregnancy, childbirth and post-delivery, establishing the Program of Humanization in Prenatal and Birth (PHPN). It is an unprecedented program, as a deep search in literature did not identify any other program like PHPN. Besides, it is a proposal of intervention for a country that is in process of development; it offers directives for the different instances of assistance; it describes the minimum conditions for the attention with financial incentive connected to the execution of such conditions; and it suggests an information system (SISPRENATAL), with offers the local administrator to monitor progress and challenges and to correct imperfections. In this context, it was decided to carry out the present study which had as a general objective to evaluate the quality of prenatal assistance in Ceará from the implementation of PHPN on. The specific objectives were to evaluate process indicators of PHPN generator in the SISPRENATAL in the State; to analyze specific aspects of the nurse’s performance in the prenatal attention, informed in the SISPRENATAL; and to identify the financial income produced by PHPN to the state of Ceará. The study was characterized as exploratory and descriptive and its universe was the Health System of Ceará. Part of the data was collected in the Information Department of the Health State Secretariat through a search in the Prenatal Information System (SISPRENATAL). The other part was collected in the Coordination of Control and Evaluation of the same Secretariat. The process indicators served as supplementary information to analyze the quality of prenatal assistance in Ceará, between June, 2001 and August, 2006. Throughout these six years 691.001 live born infants (NV) were notified in the SISPRENATAL. However, only 312.507 registrations of pregnant women were notified, that is, 44,4% of NV, including pregnant women with pregnancy age until 120 days from 2001 to 2003, and from then on women with all pregnancy ages. It was observed a continuous increase in the indicators of pregnant women’s early registration (<120 days) in the program, from 88,3%, in 2001, to 96,4%, in 2006. In the evaluation of all conditions determined in Component I of PHPN, together, which defines a better quality of prenatal assistance, the percentage reached 15,67% of registered pregnant women. This result was about 50% superior to the result found in the Country, considering that the conclusion of this indicator in national level was about 10,12% in the same period. It was demonstrated that nurses act extensively in prenatal assistance of basic health units of the State, because 95% of pregnant women’s registration and 88% of post-delivery service were carried out by this professional. Concerning the financial aspect, when we verify the difference of the value of the actions which were carried out and informed at the BPA of the municipalities but were not approved, we have a State total value of R$ 323.040,00. It is noticeable by this value the possible lack of interest or even the lack of Knowledge that governors have when solving problems that produce the disapproval of information and block the collection of resources, what decreases the possibility of greater progress in this area. In conclusion, it was possible to notice through this study that it is necessary to intensify the discussions among professionals, governors and community about progress and challenges in each municipality, in each area of PSF, in other to promote a visualization of several necessities in prenatal assistance and look for possible and effective solutions. It is unacceptable that the area of care which is so necessary and considered many times a priority by public policies suffer because of negligence and absence of basic guarantees like the realization of essential lab exams, anti-tetanus immunization and post-delivery service. This is a reality detected in Ceará and also described in the national scenery. We have to recognize the active role of the nurse in this area of care and that it is urgent that governors of the municipality appropriate the financing process of PHPN and minimize missed opportunities to obtain financial resources for the Health Local System.